Effects of dietary chlorogenic acid on ileal intestinal morphology, barrier function, immune factors and gut microbiota of broilers under high stocking density stress - Li, Yu-Qian; Zhang, Yi; Bai, Dong-Ying; Liu, Yan-Hao; He, Xiang-Long; Ito, Koichi; Liu, Ke-Xin; Tan, Hai-Qiu; Zhen, Wen-Rui; Zhang, Cai; Zhang, Bing-Kun; Ma, Yan-Bo (Frontiers in Physiology, 2023)
The purpose of this research was to assess the effect of chlorogenic acid (CGA) in the diet on ileac structure, barrier function, immunological state, and microbial profile of broiler chickens in a high stocking density (HD) environment. Four hundred and seventy-six male AA broiler chickens were randomly split into four groups, two with a normal stocking density (ND) of fourteen birds per m2 and two with a high stocking density of twenty-two birds per m2. One of the two ND and HD groups received the usual feed, while the other two were given CGA as part of their dietary regimen. The ND CGA group showed a greater increase in villus height and villus height/crypt depth compared to the ND group at 35 and 42 days. The HD group experienced a greater elevation in villus height due to CGA supplementation than the HD group across days 28, 35, and 42. At day 42, the HD group saw a decline in OCLN and ZO-1 mRNA expression in the ileum, but CGA was able to restore them. The HD group experienced a greater rise in OCLN mRNA than the control HD group when supplemented with CGA. The expression of TNF-α, IL-1β, and IL-6 in the ileum was higher in the HD group, and CGA supplementation enhanced this effect. The HD group experienced a greater rise in IL-10 mRNA expression than the control group following the administration of CGA. The HD group showed reduced alpha diversity and an increase in detrimental microbes such as Turicibacter and Shigella in the gut compared to the ND group, while the HD CGA group saw a reduction in Turicibacter, Shigella, and other harmful microbes. These findings reveal that HD stress suppressed the growth of ileac villi, decreased the expression of tight-junction genes, amplified the expression of inflammatory genes, and disturbed the gut microbiota, ultimately leading to increased intestinal permeability. We conclude that when chickens are given dietary CGA, the disruption of the ileac barrier and increased oxidative damage and inflammation due to HD stress are reduced, which increases ileac integrity and the presence of beneficial intestinal bacteria.